2012
DOI: 10.1152/jn.00073.2012
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete spinal cord injury promotes durable functional changes within the spinal locomotor circuitry

Abstract: While walking in a straight path, changes in speed result mainly from adjustments in the duration of the stance phase while the swing phase remains relatively invariant, a basic feature of the spinal central pattern generator (CPG). To produce a broad range of locomotor behaviors, the CPG has to integrate modulatory inputs from the brain and the periphery and alter these swing/stance characteristics. In the present work we raise the issue as to whether the CPG can adapt or reorganize in response to a chronic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 52 publications
5
39
0
Order By: Relevance
“…As illustrated in Figures 6 and 7 (black circles and bars), the HL coupling values and mean AIs of the Untrained Group remained unchanged between the third week after hemisection and spinalization (ANOVA, p Ͼ 0.05). This result is in accordance with our recent study (Martinez et al, 2012) showing that when no training is performed after spinalization, the asymmetries observed after hemisection are maintained after spinalization indicating that the hemisection had promoted spontaneous intraspinal reorganizations.…”
Section: Untrained Cats: Spontaneous Locomotor Recoverysupporting
confidence: 93%
See 3 more Smart Citations
“…As illustrated in Figures 6 and 7 (black circles and bars), the HL coupling values and mean AIs of the Untrained Group remained unchanged between the third week after hemisection and spinalization (ANOVA, p Ͼ 0.05). This result is in accordance with our recent study (Martinez et al, 2012) showing that when no training is performed after spinalization, the asymmetries observed after hemisection are maintained after spinalization indicating that the hemisection had promoted spontaneous intraspinal reorganizations.…”
Section: Untrained Cats: Spontaneous Locomotor Recoverysupporting
confidence: 93%
“…The second spinal lesion, this time complete, disrupted the remnant supraspinal inputs to the spinal cord and aimed at revealing the instraspinal changes that occurred between the two lesions. As showed herein and in a recent paper (Martinez et al, 2012), locomotor characteristics observed 3 weeks after hemisection were retained for a long time after spinalization but, interestingly, only on the side of the previous hemisection (left side) while the right HL made adjustments to catch up with the left HL. This retention of changes on the left side indicated that the new mode of functioning observed after hemisection was imprinted within the spinal cord and is imputable to the first iSCI because the locomotor pattern was shown to remain unchanged in spinal animals that were not submitted to a previous partial SCI (Lovely et al, 1990).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Kinematics of the distal limb could be of further potential (Moorman et al, 2012;Olsen et al, 2013). Motion capture and force plates have the potential to aid assessment of deficits in neuro-motor control on a spinal or supraspinal level because spatial and temporal characteristics are primarily controlled through the spinal and supra-spinal neural pathways (Martinez et al, 2012;Rossignol and Frigon, 2011). Classification of movement as normal, or abnormal, can be based on a combination of subjective clinical examination and objective analysis of gait (Keegan et al, 2012;Lord et al, 2013;Wren et al, 2011).…”
Section: Introductionmentioning
confidence: 99%